2014
DOI: 10.1155/2014/765784
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Increases Ceramide Synthesis in Skeletal Muscle

Abstract: Aims. The purpose of this study was to determine the effect of insulin on ceramide metabolism in skeletal muscle. Methods. Skeletal muscle cells were treated with insulin with or without palmitate for various time periods. Lipids (ceramides and TAG) were isolated and gene expression of multiple biosynthetic enzymes were quantified. Additionally, adult male mice received daily insulin injections for 14 days, followed by muscle ceramide analysis. Results. In muscle cells, insulin elicited an increase in ceramide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…In mice, we found that prolonged insulin treatment resulted in reduced glucose and insulin tolerance, suggesting that insulin alone, independent of other variables, is capable of inducing insulin resistance. This observation corroborates evidence from several previous reports in humans and rodents wherein hyperinsulinemia from endogenous (e.g., insulinoma) [ 40 ] and exogenous (e.g., injections) [ 26 , 41 , 42 ] sources causes insulin resistance. This insulin-desensitizing effect of prolonged hyperinsulinemia is likely at least partially mediated via ceramide accrual [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In mice, we found that prolonged insulin treatment resulted in reduced glucose and insulin tolerance, suggesting that insulin alone, independent of other variables, is capable of inducing insulin resistance. This observation corroborates evidence from several previous reports in humans and rodents wherein hyperinsulinemia from endogenous (e.g., insulinoma) [ 40 ] and exogenous (e.g., injections) [ 26 , 41 , 42 ] sources causes insulin resistance. This insulin-desensitizing effect of prolonged hyperinsulinemia is likely at least partially mediated via ceramide accrual [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…), insulin has distinct downstream mediators; one mediator may be the sphingolipid ceramide. Ceramides are increasingly recognized as an injurious mediator of heart pathologies [ 21 25 ] and we have recently found that insulin increases ceramide biosynthesis and accrual in skeletal muscle [ 26 , 27 ]. In light of the evidence suggesting a role for insulin in the etiology of heart complications, the purpose of these experiments was to determine the effect of insulin on heart ceramides, as well as possible ceramide-induced alterations in mitochondrial function.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Therefore, insulin is the most important factor in the regulation of plasma glucose homeostasis. Hyperinsulinemia is characterized as a condition where excess insulin is circulating in the blood, resulting from reduced sensitivity to insulin and disturbances in insulin .…”
Section: Discussionmentioning
confidence: 99%
“…The organic phase was collected in a fresh vial and dried via vacuum centrifugation (Eppendorf Concentrator Plus). Lipids were then characterized and quantified using shotgun lipidomics on a Thermo ScientificLTQ Orbitrap XL mass spectrometer, as previously described (12).…”
Section: Methodsmentioning
confidence: 99%